2012
DOI: 10.1590/s1413-35552012005000022
|View full text |Cite
|
Sign up to set email alerts
|

Do muscle strengthening exercises improve performance in the 6-minute walk test in postmenopausal women?

Abstract: Background: Walking speed seems to be related to aerobic capacity, lower limb strength, and functional mobility, however it is not clear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
15
0
4
Order By: Relevance
“…(14) Um estudo de Reis et al, (5) sugere não haver relação entre a força muscular e a capacidade funcional. A população do estudo foi de mulheres na menopausa, com média de idade 44,11±15,00.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…(14) Um estudo de Reis et al, (5) sugere não haver relação entre a força muscular e a capacidade funcional. A população do estudo foi de mulheres na menopausa, com média de idade 44,11±15,00.…”
Section: Discussionunclassified
“…(4) Na literatura atual, tem sido estudada principalmente na população idosa, portadores de doenças cardíacas e respiratórias, hipertensos e mulheres. (5)(6)(7) É possível avaliar a CF a partir de diferentes instrumentos como: testes em esteira, testes de exercício cardiopulmonar, testes de distância bidirecional, conhecido como Shuttle…”
Section: Introductionunclassified
See 2 more Smart Citations
“…One study of postmenopausal women found no effect of regular exercise and stretching on walking performance. 85 In one study of older individuals with hip flexor contracture, 8 weeks of hip and ankle stretching provided a modest improvement in passive ROM (hip 6.8°, ankle 3.5°) but failed to improve stride length. 86 In a similar study, 10 weeks of hip and ankle stretching improved hip flexibility (1.5°) but failed to show significant improvements in gait performance.…”
Section: Studies Of Specificity and Transfer In Patientsmentioning
confidence: 99%